ALGORITMA MODEL PENENTUAN LOKASI FASILITAS TUNGGAL DENGAN PROGRAM DINAMIK - Firmansyah Firmansyah; Rima Aprilia (Universitas Islam Negeri Sumatera Utara, 2018)
Facility plays an important role of the real world, the facility is no longer a secondary requirement but becomes a primary need. Provision of facilities from any company requires a competitive location, so that the facilities provided can be useful for others. Dynamic Programming was once used to determine the best opening schedule of Subset as an